CHASSIS FRAME DESIGN AND ANALYSIS BASED ON FORMULA SAE JAPAN - Irsyadi Yani; Amir Arifin; Ahmad Irham Jambak; Gunawan Gunawan; Dendy Adanta; Barlin Barlin (Indonesian Journal of Engineering and Science (IJES), 2021)
Formula Society of Automotive Engineers (FSAE) is a competition where the students design, build, and race the formula-style car. In this competition, the regulation stringent for the safety of participants. Chassis is one of the regulated parts among the other parts. This paper examines design process followed by chassis analysis by using Solidworks 2018 and Abaqus/CAE 6.14 software. The analysis process is carried out with Static Vertical Test, Torsional Stiffness Test, and Crash Impact Test using a safety standard in the form of a safety factor that must be more than 1 (SF> 1) to ensure the safety of the driver. The aim is to obtain an optimum final design based on FSAE Japan regulation as a reference for the Universitas Sriwijaya electric car team, namely Sriwijaya Eco in making the framework for the upcoming electric formula car.